Comparison of growth, hydrocarbon accumulation and metabolites of Botryococcus braunii between attached cultivation and aqueous-suspension cultivation - Pengfei, Cheng; Yan, Wang; Qiyong, Yang; Tianzhong, Liu (International Journal of Agricultural and Biological Engineering, 2017)
Botryococcus braunii is a colonial green microalga which can produce extracellular hydrocarbons at a high rate, it is considered as one of the most promising feedstocks for sustainable biofuel production. However, B. braunii is generally recognized difficulties for cultivating and has limited amount of substantive scale-up and productivity assessments with conventional aqua-suspended cultivation systems (open pond and varieties of closed photobioreactors). This paper introduces a novel cultivation system based on biofilm technology, which is called “attached cultivation”. To investigate the potential of attached cultivation method, attached cultivation of B. braunii SAG 807-1 was compared with aqueous-suspension cultivation (flat plate reactors). The growth, hydrocarbon accumulation and metabolites were studied under identical conditions (e.g. temperature, light intensity, CO2 concentration). The main research results obtained are as follows: compared with conventional aqueous-suspension cultivation, the biomass productivity of B. braunii under biofilm attached cultivation was 4.78 g/(m2•d), which was higher than of 4.43 g/(m2•d) by aqueous-suspension, and hydrocarbon productivity of the two cultivation methods were 2.52 g/(m2•d) and 2.37 g/(m2•d), respectively. The contents of carbohydrate and protein were also similar. This attached cultivation method showed a new model of commercialization for the microalgae-derived biofuels. Keywords: Botryococcus braunii, attached cultivation, aqueous-suspension cultivation DOI: 10.3965/j.ijabe.20171001.3008 Citation: Cheng P F, Wang Y, Yang Q Y, Liu T Z. Comparison of growth, hydrocarbon accumulation and metabolites of Botryococcus braunii between attached cultivation and aqueous-suspension cultivation. Int J Agric & Biol Eng, 2017; 10(1): 134–141.